Empirical Evidence for Corporate Social Responsibility in Bulgarian Companies - Bakardhieva, Radostina (Research Papers, 2018)
In the last years corporate social responsibility as a theory and practice is considered in integral unity with corporate sustainability, sustainable development and social reporting. The European agenda puts as accent non-financial reporting as a tool for legitimizing companies to society, twisting reputation of the firms and successful overcoming of non-financial risks.The goal of publication is to reveal corporate social responsibility as lever to achieve the goals of sustainable development. In the publication are presented monitoring and evaluation of external corporate social responsibility with purpose satisfaction of claims of external stakeholders targeting to ecological corporate initiatives and responsibility to local community as well impact evaluation of certain factors as number of workers and company profit. The attitudes of manager of Bulgarian firms to social responsible projects are studied. The processing of empirical date is by statistical methods.It is concluded that corporate social responsibility is a flexible tool for solving of social conflicts and overcoming of non-financial risks.